PENGAWASAN WALI MURID SDN 46 BATU HAMPAR DALAM PENGGUNAAN INTERNET - Elvi Rahmi (El-Rusyd, 2017)
The Internet is already familiar in the ears of students present. Since theinitial entry into Indonesia, the internet is constantly undergoing rapid growth.The rapid development of technology, the more the problems that accompanysuch misuse of the Internet for fraud, kidnapping, cyber crime, and so on. Thenegative impact of the internet is usually caused by lack of understanding ofstudents utilizing information technology, for example, playing online games andfacebook